Arquitectura y contexto arqueológico, Sector VIII, andenes «Las Llamas» de Choquequirao - Echevarría López, Gori Tumi (2008)
This article treats brings over of the monumental architecture of the Sector the VIIIth of Choquequirao, an archaeological accession complex located in the basin of the river Apurímac, in the department of the Cusco. This sector is one of the most important of Choquequirao since presents the only wall decorations on a large scale recognized for a site Tawantinsuyu. The final result of the study revealed formal parameters of the growth and architectural development of this sector, exposing the notable relations of this process with the archaeological general accession, establishing the bases for a cultural definition and a recognition of his possible chronology.